2007
DOI: 10.1248/jhs.53.655
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Activity of Methanol Leaf Extract of Costus pictus D. DON in Alloxan-induced Diabetic Rats

Abstract: The methanol extract of Costus pictus (C. pictus) D.DON (Family: Zingiberaceae) leaf was investigated for its anti-diabetic effect in Wistar Albino rats. Diabetes was induced in Albino rats by administration of single doses of alloxan monohydrate (120 mg/kg, i.p.). The methanol extract of C. pictus (MECP) at a dose of 120 mg/kg, p.o. was administered as single dose per day to diabetes-induced rats for a period of 21 days. The effect of MECP leaf extract on blood glucose, plasma insulin, serum lipid profile [ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 27 publications
2
56
0
1
Order By: Relevance
“…Thus, 28 d oral administration of the same aqueous CP extract as used in the current study to hyperglycemic rats at 2 gm/kg body weight induced a significant (p<0.001) reduction in fasting blood glucose levels, associated with increased serum insulin levels [11]. Other studies have also reported similar results [10][11][12]. It is difficult to investigate cellular mechanisms of action using in vivo models, so in our current study we investigated the acute effect of a CP extract in vitro using MIN6 cells and primary mouse and human islets.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, 28 d oral administration of the same aqueous CP extract as used in the current study to hyperglycemic rats at 2 gm/kg body weight induced a significant (p<0.001) reduction in fasting blood glucose levels, associated with increased serum insulin levels [11]. Other studies have also reported similar results [10][11][12]. It is difficult to investigate cellular mechanisms of action using in vivo models, so in our current study we investigated the acute effect of a CP extract in vitro using MIN6 cells and primary mouse and human islets.…”
Section: Discussionsupporting
confidence: 70%
“…The plant, commonly known as spiral ginger, belongs to the Costaceae family and grows in gardens as an ornamental climbing plant [8][9]. The antidiabetic activity of a CP extract has been tested chronically in animals in vivo, where it was reported to reduce blood glucose levels in rats in which hyperglycemia had been induced by administering the -cell toxins alloxan or streptozotocin (STZ) [10][11][12]. The precise mechanism of the glucoselowering effect of CP is not completely clear but it may be due to 1) an inhibition of -amylase and -glucosidase enzymes resulting in reduced carbohydrate absorption [13]; 2) an increase in GLUT4 translocation and glucose uptake in insulin-responsive target tissues [14]; or 3) a direct stimulation of insulin secretion from pancreaticcells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Es una especie originaria de México, utilizada en la India como ornamental, en donde la gente local come las hojas y la raíz como antihelmíntico; su propagación es muy rápida en suelo, por medio de raíces y vástagos; los extractos de sus hojas presentan actividad hipoglucemiante, por lo que es importante la promoción de su cultivo, para así hacer crecer el desarrollo y disponibilidad de una medicina natural para pacientes diabéticos (Benny, 2004). De igual manera se han demostrado sus efectos antidiabéticos con extractos de hojas, presentando reducción de glucosa y lípidos en sangre, incremento en niveles de insulina plasmática, proteínas y glucógeno hepático, sin efectos tóxicos en riñón, hígado y páncreas (Jothivel et al, 2007). Si bien, en Cantarranas, C. scaber es utilizada para tratar afecciones renales, debe considerarse que este es uno de los principales padecimientos ocasionados por la diabetes mellitus (Nathan, 1996).…”
Section: Discussionunclassified
“…The methanol extract of C. pictus leaves when administered as single dose per day to diabetesinduced rats for 21 days elicited significant reductions of blood glucose, thus C. pictus leaves seem to be good anti-diabetic agent (Jothivel et al, 2007) 48 .…”
Section: Ethnobotanical Importances Of Costus Sppmentioning
confidence: 99%